Perspective In History : Essays In Honour Of Professor Obaro Ikime - Ed. Ekoko, A E and Agbi, S O (Heinemann Educational Books Ltd, 1992)
This book is written by renowned scholars to commemorate Professor Ikime's 50th birthday.The book is also an attempt by the contributors to pay tribute to the academic excellence of a devoted teacher.
Keywords: Essays; Literary Collections; Non Fiction